The Source of Anodic Hydrogen Evolution on Ultra High Purity Magnesium. (10th September 2016) - Fajardo, S.; Glover, C.F.; Williams, G.; Frankel, G.S.
Abstract: The enhanced catalytic activity of hydrogen evolution reaction on anodically polarized Mg surfaces, commonly referred to as the Negative Difference Effect, has been the topic of intense investigation in recent years. However, the cause of anodic H2 remains unclear. To determine the primary source of H2 evolution on dissolving Mg polarized at anodic potentials, an in-situ scanning vibrating electrode technique (SVET) analysis during galvanostatic polarization, coupled with gravimetric H2 volume collection and potentiodynamic polarization experiments, were carried out on ultra-high purity Mg (99.9999% Mg). The combination of these methods provided solid evidence that the evolution of hydrogen on dissolving ultra-pure Mg is primarily associated with the regions dominated by the anodic reaction. Although local cathodes corresponding with the dark corrosion film formed during anodic dissolution were revealed by in-situ SVET, they appeared to play a minor role in the process.